SUSTAINED CHARACTER BUILDING THROUGH LITERATURE FOR COLLEGE STUDENTS IN INDONESIA - Hariyanti, Tatit; Sudjito, Sudjito (Jurnal Dinamika Hukum, 2018)
This article aims at promoting sustained character building through literature especially for college students in Indonesia. Till present, the character building has been restricted to the embedment of good virtues to children and adolescents. The majority of existing studies and researches, therefore, tend to focus their attention on such limited area. Character building ought to be a sustainable effort halted not when one finishes his/her study at elementary or intermediate grades. It should be maintained all life long. There are two highlighted problems which are going to explore in this paper: first, why literature is still considered to be one of the effective media to establish sustained character building for college students and second, what appropriate Instructional Strategies to conduct such effort are. The result shows that literature is still effective due to its natural characteristics, its wide spectrum, and its dynamically broadened functions. Under the conviction that the students have already been undergoing the process of embedment of some core values before, the given literary works containing, elaborating and questioning or challenging the given embedded values are taken to be the source of discussion. The instructional strategies cover discussion, debate, seminar, film appreciation, and creative writing.Keywords: character building, instructional strategies, literature, sustained